Constructing Motivation for Sports Activities among College Students using CB-SEM Path Model - Zaini, Bahtiar Jamili; Md Yusof, Zahayu; Mansor, Rosnalini; Zainuddin, Norzairiah; Khairul Adlee, Nurul Faziera; Lop Ahmad, Hanun Nasuha (EJEMCM, 2020)
Sports is a physical activity that allows members to encounter enjoyment and competition, while simultaneously gaining positive results. This study proposed to investigate the factors affecting students’ motivation in sports activities, hence identifying the relationship between these factors and to develop a conceptual model to help in explaining students’ motivation towards sports activities. A quantitative research design was chosen, and the respondents were (N=204) CollegeStudents in Universiti Utara Malaysia. The responses towards the questionnaire will be illustrated in semantic scale between 1 and 7. Structural equation modelling was used to model the self-administered research questions. The results demonstrated that all factors have direct influence towards students’ motivation in sportsactivities and that self-appearance is the highest factor that contributes to students’ motivation towards sportsactivities. This study can also be used to help students to raise their motivations towards sports activities